Socio-Sufistic Trends of Marriage in Creating Harmony in the Postmodern Society of Kampung Arab, Madura: A Perspective on the Theory of Utilitarianism - Abitolkha, Amir Maliki; Dodi, Limas (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Divorce in families is caused by conflict, while conflict is caused by the fallacy of the postmodern society's perspective that believes that the logic of science by ignoring God's function as a supernatural force. This study aims to reaffirm that Sufism is a value as well as a discipline that can create harmony in postmodern society. The research method used is qualitative-phenomenological, analyzed using the theory of utilitarianism. Data collection techniques through interviews, observations and documentation. The findings of this study are that 1) sufism is internalized to society as a basis of value. Marriage is a sacred and accountable covenant with the Lord. Marriage is seen as a means of achieving God's pleasure, not merely a relationship between man and man; 2) the rule of law is the process of achieving a goal, not a final rule that cannot be contextualized in a postmodern context. The rights and obligations of husbands and wives can be adjusted to the sufistic attitudes of postmodern society that has a high work ethic, is optimistic and pro-active in making a family living. As a process, the rule of law is subjective and the existence of other processes with the same purpose becomes common. 3) the law aims at creating happiness whose ultimate goal is harmony. Then the process on any basis, culture, character, customary law, if it can bring happiness is socially valid.